Narrative medicine educational project to improve the care of patients with chronic obstructive pulmonary disease. Issue 2 (4th May 2018) - Cappuccio, Antonietta; Sanduzzi Zamparelli, Alessandro; Verga, Massimo; Nardini, Stefano; Policreti, Alessandro; Porpiglia, Pasquale Alberto; Napolitano, Silvia; Marini, Maria Giulia
Chronic obstructive pulmonary disease (COPD) is characterised by a progressive loss of pulmonary function. Often patients do not adhere to inhaled therapies and this leads clinicians to switch treatments in order to improve control of the symptoms. Narrative medicine is a useful approach that helps healthcare professionals to think over the doctor–patient relationship and how patients live with their disease. The aim of this training project was to teach pulmonologists the basics of narrative medicine: to carefully listen to patients and to practice reflective writing in their relationship with them. Training on narrative medicine and parallel charts was provided through a webinar and a weekly newsletter. Across 362 narratives, written by 74 Italian pulmonologists, 92% of patients had activity limitations at their first visit. The main factor influencing the effectiveness and adherence to therapy was a positive doctor–patient relationship; indeed, if such relationship is difficult, only 21% of patients are able to resume all their activities. After learning the narrative approach, clinicians became aware of the need to spend more time listening to patients, to reflect through writing and to understand more deeply the motivations that lead people towards adherence to new therapies. The experience of 79 Italian pulmonologists using the narrative medicine approach in COPD http://ow.ly/NfnY30jdEpS